High Performance Computing in Science and Engineering ’99: Transactions of the High Performance Computing Center Stuttgart (HLRS) 1999 - Krause, Egon; Jäger, Willi (Springer Berlin Heidelberg, 2000)
The book contains reports about the most significant projects from science and engineering of the Federal High Performance Computing Center Stuttgart (HLRS). They were carefully selected in a peer-review process and are showcases of an innovative combination of state-of-the-art modeling, novel algorithms and the use of leading-edge parallel computer technology. The projects of HLRS are using supercomputer systems operated jointly by university and industry and therefore a special emphasis has been put on the industrial relevance of results and methods